Land Suitability Evaluation for Durian Cultivation in Universitas Muhammadiyah Mataram Educational Forest (KHDTK UMMAT) - Ahmad Fatoni; Erni Romansyah; Suhairin Suhairin; Ida Wahyuni; Hasanuddin Molo; Ahmad Suriadi (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2025)
The Forest Area with Special Educational Purposes (KHDTK) at Muhammadiyah University of Mataram, covering 93.55 hectares, has undergone enrichment with eucalyptus and agarwood plants since 2019. In 2024, further enrichment is planned with durian, avocado, jackfruit, and longan. However, concerns have arisen regarding the suitability of the KHDTK area for durian cultivation, necessitating a land suitability evaluation. This study aims to determine the suitability classes, limiting factors, and management recommendations for durian and other selected plants. Using a rigid grid method, a soil survey and evaluation were conducted, assessing 14 parameters related to soil, climate, and land. The findings indicate that the land suitability for durian falls into class S3, with limiting factors including coarse soil texture, low levels of nitrogen, phosphorus, and potassium, insufficient rainfall, and a slope of 16-30%. Recommended management strategies include the application of organic and NPK fertilizers, installation of pipe irrigation, and contour-aligned planting. Enrichment with durian in the KHDTK area is suggested to be developed. This study contributes to sustainable land management by providing scientific data for durian cultivation in KHDTK areas. In addition, the results can support the development of conservation-based agroforestry and agritourism.